Vaccination with conserved regions of erythrocyte-binding antigens induces neutralizing antibodies against multiple strains of Plasmodium falciparum. - Julie Healer; Jennifer K Thompson; David T Riglar; Danny W Wilson; Yu-H C Chiu; Kazutoyo Miura; Lin Chen; Anthony N Hodder; Carole A Long; Diana S Hansen; Jake Baum; Alan F Cowman (PLoS ONE)
Background A highly effective vaccine against Plasmodium falciparum malaria should induce potent, strain transcending immunity that broadly protects against the diverse population of parasites circulating globally. We aimed to identify vaccine candidates that fulfill the criteria. Methods We have measured growth inhibitory activity of antibodies raised to a range of antigens to identify those that can efficiently block merozoite invasion for geographically diverse strains of P. falciparum. Results This has shown that the conserved Region III-V, of the P. falciparum erythrocyte-binding antigen (EBA)-175 was able to induce antibodies that potently inhibit merozoite invasion across diverse parasite strains, including those reliant on invasion pathways independent of EBA-175 function. Additionally, the conserved RIII-V domain of EBA-140 also induced antibodies with strong in vitro parasite growth inhibitory activity. Conclusion We identify an alternative, highly conserved region (RIV-V) of EBA-175, present in all EBA proteins, that is the target of potent, strain transcending neutralizing antibodies, that represents a strong candidate for development as a component in a malaria vaccine.